Methods of condom distribution as a possible barrier to condom uptake : a study among sexually active clients at Settlers Hospital Grahamstown - Megafu, Sylvester Onyechi (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.